Effect of Nitrogen additional fertilization on Downy Mildew Disease development, Yield, productivity of Cucumbers under plastic Greenhouse. - علاف عصام (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out in Al-Jumisiyah (Tartous governorate), in a greenhouse during 2020/2021, in order to determine the effect of different levels of additional nitrogen fertilization on the prevalence of downy mildew disease on cucumber plants grown in greenhouses and the effect of the development of the infection on the growth and productivity of the plant. Experience included four treatments with four replications in which three rates of urea fertilizer 46% (8, 16 and 24 g/m2) were used in addition to the unfertilized control. The experiment was designed according to a randomized complete block design. As a result of the study, it was found an increase in the rate of infection of cucumber plants with the disease (46, 56.6 and 60.7%) and the severity of infection reached (13.3, 20 and 42.3%), with significant differences compared with the control, and this was accompanied by a decrease in cucumber production amounting to 4 and 13. 37 and 40.39% in the three fertilizer treatments, N1, N2, and N3, respectively, compared to the untreated control, whose average yield was 5.035 kg/m2.